Changes in free amino acid profile in goats with pregnancy toxemia - Uztimur, Murat; Gazioglu, Abdullah; Yilmaz, Okkes (Springer, 2024)
Pregnancy toxemia is a metabolic disorder that afflicts goats when the heightened energy requirements preceding parturition are not sufficiently satisfied. At present, the potential association between pregnancy toxemia and the free amino acid composition in hair goats remains uncharted territory. The purpose of this study is to investigate the free amino acid profile in goats during the pivotal three weeks preceding delivery, distinguishing among those with subclinical pregnancy toxemia (SPT), clinical pregnancy toxemia (CPT), and those in the control group (CG). Additionally, the study aims to investigate any potential relationship between the amino acid profile and beta hydroxy butyric acid (BHBA) levels. The researchers analyzed a total of 50 goats, comprising 20 goats with SPT, 20 with CPT, and 10 in the CG. The serum free amino acid profile was determined using a gas chromatography flame ionization detector (GC-FID) device. BHBA concentration in goats with CPT and SPT was significantly higher than KG (p < 0.001). Furthermore, in goats with CPT, the glucose concentration was significantly lower than in CG (p < 0.012). In goats with CPT and SPT, the concentration of valine, one of the gluconeogenic amino acids, was significantly higher than in control group (p < 0.001), while histidine concentration was significantly lower (p < 0.020) than in control group. Specifically in goats with CPT, the concentrations of alanine (p < 0.002), serine (p < 0.001), and threonine (p < 0.043) were significantly lower than in control group. Moreover, the concentration of phenylalanine, which is both a glycogenic and ketogenic amino acid, was significantly lower (p < 0.028) in goats with SPT compared to the control group. The Fisher ratio (p < 0.010) and Glycine/Alanine ratio (p < 0.001) were significantly higher in pregnancy toxemia goats with than in control group goats, indicating a poor nutritional and energy status of the goats during the prepartum period. In summation, the findings of this study underscore that amino acids exhibiting marked concentration variations hold considerable promise in the diagnosis, prognosis, and therapeutic management of pregnancy toxemia.
Keywords: Goat; Pregnancy toxemia; Amino acid profile; BHBA